Pancasila Sebagai Tameng Budaya di Badai Global: Menjaga Warisan, Merangkul Perubahan, Eksistensi Kearifan Lokal di Dunia Tanpa Batas - Yosua Hasiholan Simatupang (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Indonesia is a diverse nation, comprised of thousands of ethnicities and cultures, adding to the country's diversity and richness. Multiculturalism is the identity and image of the Indonesian nation, a characteristic of the country thanks to its rich local wisdom. Above all differences, Pancasila, the foundation of the state, and Bhinneka Tunggal Ika, the national motto, serve as a unifying force for the Indonesian people. Local wisdom is a philosophy of life, ethical values, and life strategies passed down through generations, created through the harmonious interaction of society with its natural and social environment. In terms of identity, local wisdom serves as a marker of a community's identity and distinguishes it from other cultures. Global popular culture flows primarily through social media, film, music, and the mass media. Younger generations often find it easier to adopt modern culture because it is considered more practical and in keeping with today's lifestyles.